2007
DOI: 10.1017/s0033291707001730
|View full text |Cite
|
Sign up to set email alerts
|

Measuring depression: comparison and integration of three scales in the GENDEP study

Abstract: The MADRS and the BDI can be recommended as complementary measures of depression severity. The three factor scores are proposed for external validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(251 citation statements)
references
References 33 publications
6
232
0
8
Order By: Relevance
“…The content and psychometric properties of different scales used to measure depression are a relevant example. The HRSD had long been seen as the "gold standard" for depression research, but more recently was shown to be less accurate and less internally consistent than the BDI and the MADRS, potentially not valid for use in outpatient samples (Uher et al, 2008). …”
Section: Methodological Issuesmentioning
confidence: 99%
“…The content and psychometric properties of different scales used to measure depression are a relevant example. The HRSD had long been seen as the "gold standard" for depression research, but more recently was shown to be less accurate and less internally consistent than the BDI and the MADRS, potentially not valid for use in outpatient samples (Uher et al, 2008). …”
Section: Methodological Issuesmentioning
confidence: 99%
“…27 Previous psychometric analyses of the MADRS using the GENDEP data showed this rating scale had the greatest internal consistency of the three measures. 28 As the MADRS was also designed specifically to be sensitive to change over time, 25 in this report, participants' weekly MADRS score was used as the primary measure of their response to both antidepressants.…”
Section: Methodsmentioning
confidence: 99%
“…Radloff, for instance, recommended to describe the CES-D with 4 factors, Beck suggested to extract at least two factors for the BDI, and Rush et al identified 3 factors in their psychometric study of the IDS-30 (Rush et al, 1996). Multifactorial results also emerge when symptoms of several questionnaire are pooled (Uher et al, 2008).…”
Section: Unidimensionalitymentioning
confidence: 99%